2018
DOI: 10.1073/pnas.1813000115
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-based materials fuel human stem cells by metabonegenic regulation

Abstract: A comprehensive understanding of the key microenvironmental signals regulating bone regeneration is pivotal for the effective design of bioinspired orthopedic materials. Here, we identified citrate as an osteopromotive factor and revealed its metabonegenic role in mediating citrate metabolism and its downstream effects on the osteogenic differentiation of human mesenchymal stem cells (hMSCs). Our studies show that extracellular citrate uptake through solute carrier family 13, member 5 (SLC13a5) supports osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 47 publications
5
123
0
Order By: Relevance
“…The altered eccentricity and perimeter of Ank ank/ank femora are most likely a result of compensatory bone remodeling to retain whole bone strength. Interestingly, Ma et al recently reported that local levels of extracellular citrate are important for the osteogenic development of human mesenchymal stem cells [16]. Kim et al showed that differentiation of osteoblast is delayed in mice lacking Ank, which was attributed to reduced extracellular levels of PPi [11].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…The altered eccentricity and perimeter of Ank ank/ank femora are most likely a result of compensatory bone remodeling to retain whole bone strength. Interestingly, Ma et al recently reported that local levels of extracellular citrate are important for the osteogenic development of human mesenchymal stem cells [16]. Kim et al showed that differentiation of osteoblast is delayed in mice lacking Ank, which was attributed to reduced extracellular levels of PPi [11].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Like PPi, citrate is also one of the major organic compounds present in bone and also strongly associates with hydroxyapatite 16 . With 90% of the body’s citrate content present in bone, this tissue is thought to play a central role in extracellular citrate homeostasis 17 . Therefore, we determined if bone citrate levels depend on ANK.…”
Section: Resultsmentioning
confidence: 99%
“…The altered eccentricity and perimeter of Ank ank/ank femora are most likely a result of compensatory bone remodeling to retain whole bone strength without increasing total bone mass. Interestingly, Ma et al recently reported that local levels of extracellular citrate are also important for the osteogenic development of human mesenchymal stem cells 17 . It is therefore conceivable that ANKH-dependent citrate release into bone is not only important for the material properties of hydroxyapatite, but also contributes to osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, one can envisage that the releasing of metabolic regulators, such as ions, metabolites and O 2 , which are inherently embedded or incorporated in biomaterials, may modulate intracellular metabolic flux after entering cells. In fact, metabolic regulator release represents the primary conduit through which biomaterials affect cell metabolism and subsequently influence cell functions, which is of particular interest for regenerative engineering.…”
Section: Harnessing Biomaterials Cues For Metabolic Regulationmentioning
confidence: 99%
“…Within the pool of degradation products that are gradually and dynamically released into the extracellular space in situ overtime, there may be metabolic regulators including regulatory metabolites, cofactors, and key substrates for energy production or biosynthesis that can impact intracellular metabolic events. Indeed, we recently identified citrate in the degradation products of citrate‐based biomaterials (CBBs) as this type of inherent metabolic regulator for hMSCs bioenergetics toward facilitated osteogenic differentiation via a mechanism named “metabonegenic” regulation ( Figure Ai) . Intracellular citrate is well‐known as an intermediate metabolite, playing an important role in regulating energy homeostasis, since it not only modulates the activity of key enzymes in both catabolic and anabolic pathways, but also could convert to acetyl–CoA, the direct substrate for fatty acid biosynthesis and histone acetylation .…”
Section: Harnessing Biomaterials Cues For Metabolic Regulationmentioning
confidence: 99%